Peran Keluarga dalam Pendidikan Informal Remaja untuk Menanamkan Nilai Toleransi di Masyarakat Plural - Sabirah Lathifah Zahra Nasution; Nabila Shakira Daulay; Nazla Balqis; Nayla Khanza Syahputri; Bisru Hafi (Alpatih Harapan Semesta, 2026)
This study was conducted in response to the growing challenges of intolerance among adolescents in the digital era, influenced by social media, stereotypes, and social polarization within diverse communities. The research aimed to analyze the role of the family as an informal educational institution in fostering tolerance values among adolescents. A qualitative method with a phenomenological approach was employed. Data were collected through semi-structured interviews with ten informants selected using purposive sampling. The data were analyzed through data reduction, data display, and conclusion drawing. The findings revealed that families play a vital role in developing adolescents’ tolerance through parental role modeling, open communication, and the cultivation of respect for differences in daily life. However, social media and peer influences may hinder the internalization of tolerance values when not accompanied by adequate parental supervision. The study concludes that the family serves as a key foundation in shaping a tolerant, open-minded generation capable of living harmoniously in a multicultural society.